Pre-Service English Teachers’ Acculturation into School Teaching Practice during Internship: A Narrative Case Study - Zhang, Ruyue; Huang, Fang (Social Education Research, 2022)
Given the lack of research inquiring into pre-service teachers’ acculturation, this study explored pre-service English teachers’ acculturation into teaching practice during their internship in the Chinese context. A qualitative case study was conducted among two intern English teachers, with data obtained from semi-structured interviews. The findings revealed that pre-service intern English teachers perceived uncertainties and confusion, they encountered difficulties when acculturating into school teaching practice, including acculturation into the new living situations, psychological well-being adaptation, identity transformation, and the handling of interpersonal relations. Possible reasons for these difficulties include divergence in value orientations, unprepared mindset and professional identity, and insufficient cooperation among teacher-training universities, the administrative departments of government, and local schools. The results of the study provide pre-service teachers with suggestions to effectively acculturate into teaching practice during the internship, but also provide suggestions for universities and local schools to make informed decisions.